Thermodynamic and crystallographic model for anion uptake by hydrated calcium aluminate (AFm): an example of molybdenum - Marty, Nicolas C. M. (Sci Rep, 2018)
Amongst all cement phases, hydrated calcium aluminate (AFm) plays a major role in the retention of anionic species. Molybdenum (Mo), whose (93)Mo isotope is considered a major steel activation product, will be released mainly under the form of MoO(4)(2−) in a radioactive waste repository. Understanding its fate is of primary importance in a safety analysis of such disposal. This necessitates models that can both predict quantitatively the sorption of Mo by AFm and determine the nature of the sorption process (i.e., reversible adsorption or incorporation). This study investigated the Cl(−)/MoO(4)(2−) exchange processes occurring in an AFm initially containing interlayer Cl in alkaline conditions using flow-through experiments. The evolution of the solid phase was characterized using an electron probe microanalyzer and synchrotron high-energy X-ray scattering. All data, together with their quantitative modeling, coherently indicated that Mo replaced Cl in the AFm interlayer. The structure of the interlayer is described with unprecedented atomic-scale detail based on a combination of real- and reciprocal-space analyses of total X-ray scattering data. In addition, modeling of several independent chemical experiments elucidated that Cl(−)/OH(−) exchange processes occur together with Cl(−)/MoO(4)(2−) exchange. This competitive effect must be considered when determining the Cl(−)/MoO(4)(2−) selectivity constant.